2017
DOI: 10.1111/jre.12488
|View full text |Cite
|
Sign up to set email alerts
|

Tumor necrosis factor‐alpha inhibits osteogenic differentiation of pre‐osteoblasts by downregulation of EphB4 signaling via activated nuclear factor‐kappaB signaling pathway

Abstract: Background and Objective The majority of experiments show that tumor necrosis factor‐alpha (TNF‐α) inhibits osteogenic differentiation of mesenchymal stem cells and pre‐osteoblasts by activated nuclear factor‐kappaB (NF‐κB) signaling. However, the underlying mechanisms by which NF‐κB signaling inhibits osteogenic differentiation are not fully understood. The aim of the present study was to investigate whether EphB4 signaling inhibition mediates the effects of TNF‐α‐activated NF‐κB signaling on osteogenic diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 36 publications
1
18
0
Order By: Relevance
“…In fact, several studies have shown the effect of the NF-κB signaling pathway on osteogenic differentiation. For instance, the osteogenic differentiation of pre-osteoblasts was repressed through the activation of the NF-κB signaling pathway [27]. Another study evidenced that the taxifolin-inactivated NF-κB signaling pathway promoted osteogenic differentiation of hBMSCs [28].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, several studies have shown the effect of the NF-κB signaling pathway on osteogenic differentiation. For instance, the osteogenic differentiation of pre-osteoblasts was repressed through the activation of the NF-κB signaling pathway [27]. Another study evidenced that the taxifolin-inactivated NF-κB signaling pathway promoted osteogenic differentiation of hBMSCs [28].…”
Section: Discussionmentioning
confidence: 99%
“…However, hypoxia inducible factor-1α (HIF-1α) is engaged in bone metastasis of lung cancer through promoting the expression and secretion of Sema4D to inhibit osteogenic differentiation (35). Besides, dickkopfrelated protein 1 (DKK1) (36) and tumor necrosis factor-α (TNF-α) (37) have been proved to be involved in inhibiting osteoblast differentiation.…”
Section: Osteolytic Metastasismentioning
confidence: 99%
“…7 There is considerable evidence that TNF-a inhibits osteogenesis. 8,9 Lee et al 10 showed that exposure to TNF-a led to restrained osteoblast differentiation under various inflammatory conditions. Chen et al 11 demonstrated that osteogenic capability of PDLSCs from patients with periodontitis was markedly diminished compared with individuals with good periodontal health.…”
Section: Introductionmentioning
confidence: 99%